Analisis Tingkat Risiko Bahaya K3 Pada Pemanfaatan Bangunan Dengan Metode Hazard Operability Study (HAZOP) (Studi Kasus: Hotel Z Palangka Raya) - Baponzel, Apri Rifkha; Puspasari, Veronika Happy; Waluyo, Rudi (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2025)
sector. Hotels, as accommodation providers, must implement OHS to ensure a safe and healthy environment for workers and guests, while also boosting productivity. OHS is essential not only during construction but also in the operational phase to minimize risks and incidents that may harm hotel operations. This study aims to analyze OHS hazard risks at Z Hotel, located in Palangka Raya, Central Kalimantan. The research was conducted from November 28, 2024, to January 18, 2025, through direct observation and interviews with hotel staff, including the Manager, Office Boy, Housekeeping, and Kitchen Staff. Data were analyzed using the Hazard and Operability Study (HAZOP) method to identify potential hazards, root causes, and assess likelihood and consequences. Results showed 8 high, 11 medium, and 2 low-risk categories, with 55% categorized as high. Recommendations include the use of Personal Protective Equipment (PPE), installation of safety signs, renovation of high-risk areas, and improvements to acoustics and toilet flooring to reduce potential hazards.